Effects of regulated deficit irrigation on the growth and berry composition of Cabernet Sauvignon in Ningxia - Wang, Rui; Yan, Pengke; Sun, Quan; Su, Baofeng; Zhang, Junxiang (International Journal of Agricultural and Biological Engineering, 2019)
The adoption of water-saving irrigation strategies is required particularly for wine grape variety, which has been widely cultivated in arid and semiarid areas. To assess vine response to regulated deficit irrigation (RDI), the grape growth and berry composition under five treatments that irrigated at a certain percentage of the crop evapotranspiration (ETc) were evaluated over a 3-year period in a vineyard with the grape variety of Cabernet Sauvignon. The results indicated that RDI had a significant effect on the grape berry size and yield. The largest berry size (12.20 mm) was obtained under the T50 in 2014, while the smallest berry size (9.83 mm) one was obtained under the CK treatments in the same season. The highest individual yield occurred in the T50 treatment, with an average of 1.99 kg, followed by the T25-50 treatment. However, both weights were significantly larger than that of the CK treatment. Compared with the T50 treatments, the individual grape vine yield in the T50-25 treatments were slightly less by 16.9% for 2013, 15.3% for 2014 and 18.1% for 2015. Compared to control (CK) treatment, the soluble solid and reducing sugar contents decreased, the total acid content increased, and the sugar/acid ratio basically showed a downward trend. The treatment irrigated at 50% ETc until veraison and 25% thereafter (T50-25) increased the phenolic compound content in grape skins. The treatment received only rain water during the grape growing season (CK) and the one irrigated at 25% of the ETc crop evapotranspiration (T25) caused defoliation and negatively affected the yields and grape composition during all 3 years. Therefore, the RDI not only inhibited the vine vegetative growth but also improved the fruit quality. In terms of productivity and grape composition, the Cabernet Sauvignon grape variety was most sensitive to water stress post-veraison. Over the comprehensive consideration of yield, water-use efficiency and berry composition, the T50-25 treatment was the most efficient irrigation strategy in this area. Keywords: regulated deficit irrigation, Cabernet Sauvignon, arid area, grape composition DOI: 10.25165/j.ijabe.20191206.5206 Citation: Wang R, Yan P K, Sun Q, Su B F, Zhang J X. Effects of regulated deficit irrigation on the growth and berry composition of Cabernet Sauvignon in Ningxia. Int J Agric & Biol Eng, 2019; 12(6): 102–109.